An amperometric enzyme electrode for the detection of L-lactate - Selkirk, Jane Yvonne (Cranfield University, 1997)
The main tasks of this thesis were to evaluate a number of amperometric enzyme electrode chemistries for the selective and sensitive detection of L-lactate, and apply mass fabrication technologies to reproducibly manufacture sensors in a controllable manner. The sensors studied were based on the use of lactate oxidase with a range of modified-carbon electrodes. Noble metals, hexacyanoferrate (111) or Prussian Blue were used to modify carbon electrodes for the electro-catalytic determination of hydrogen peroxide, the product of the reaction of lactate oxidase with L-lactate. Tetrathiafulvalene was employed as an artificial mediator between the enzyme and the electrode. Polypyrrole was tested as a means of immobilising lactate oxidase and to achieve direct charge transfer to the underlying carbon electrode. The characteristics of the sensor responses to hydrogen peroxide, L-lactate and ascorbate were compared, in relation to the electrochemical electrode area. From this investigation, it was confirmed that screen-printed electrodes were more reproducible to manufacture than hand-fabricated electrodes. For screen-printed rhodinised-carbon electrodes, an operating potential of +400 mV (SCE) was selected. Interference from ascorbic acid and sensitivity to hydrogen peroxide were deten-nined to be 26 gA. mM-' CM-2 and 27 gA. mM-'. CM-2, respectively. Screen-printed carbon electrodes modified with platinum, rhodium or palladium were selected for further investigation. Rhodium on carbon performed the best in ten-ns of sensitivity and selectivity at low potentials, and different formations of rhodium-carbon complexes were studied. Although rhodium electroplated onto carbon screen-printed electrodes was examined, printing inks made from a preformed powder of rhodium on carbon-graphite proved to be the preferred route of electrode fabrication. Screen printing, ink-jet printing and Cavro solution deposition were employed to fabricate the amperometric enzyme electrodes. These sensors were composed of rhodinised carbon and lactate oxidase in a water-based electrode ink with a protective outer membrane layer. Each stage, from ink preparation to membrane composition, was developed empirically. The sensitivity, stability and reproducibility of the working electrode was improved by altering it to a homogeneous ink, consisting of carbon graphite powder, rhodinised carbon powder (5% Rh by weight), hydroxyethyl cellulose (2% w/v) and lactate oxidase in the weight ratio of 2: 8: 18: 1. A layer of cellulose acetate (2% w/v in a 1: 1 solution of acetone to cyclohexanone) and an outer coating of a polyurethane called Pellethane (I% to 4% w/v in dimethyl formarnide and tetrahydrofuran) improved the selectivity, sensitivity and detection range of the sensor, allowing it to operate in physiological solutions with reduced passivation from protein adsorption. The sensor design was revised to allow its passage through a catheter and operation within a blood vessel; it was manufactured on flexible material using screen printing and Cavro solution deposition techniques. These miniature sensors, with a working surface of 0.5 x 15 mm, were capable of linearly measuring lactate up to 3 mM in buffer solutions with an average sensitivity of 44.8 nA. mM-1 L- actate. To test the sensor operation in physiological solutions, a flow injection system was employed. A planar three-electrode card used in this system was manufactured using screen printing and Cavro solution deposition techniques. L-lactate concentrations up to 6.4 mM were sensitively and, after minor correction, accurately determined in undiluted plasma and whole blood samples. This thesis has therefore made progress toward mass fabricating an amperometric enzyme electrode device suitable for the deten-nination of L-lactate concentrations in vitro.